THE DIFFERENCE OF SLEEP QUALITY BEFORE AND AFTER SKIPPING EXERCISE IN MEDICAL STUDENTS OF DIPONEGORO UNIVERSITY - Julsyawiah Novthalia; Buwono Puruhito; Dodik Pramono; Endang Kumaidah (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background : The many tasks that put upon the medical students require them to have a good sleep quality. Medical students generally have poor sleep quality. One way to improve sleep quality is to perform effective aerobic physical activities such as skipping. Aim : To explore the difference in sleep quality before and after skipping exercise in Medical Student of Diponegoro University. Methods : This study was a quasi-experimental with pre-test and post-test non-equivalent group. The samples were students of Faculty of Medicine, Diponegoro University (n = 48) aged 18-22 years who met the inclusion criteria. The sample was divided into 2 groups: control and treatment groups, each consisting of 24 students. Sleep quality score was measured using the Pittsburgh Sleep Quality Index (PSQI). The normality test was performed using the Shapiro-Wilk test. Hypothesis testing of sleep quality score before and after skipping exercise in the control group was performed using the Wilcoxon test, while in the treatment group using the paired t-test. The difference in sleep quality score between control and treatment groups was performed using the Mann-Whitney test. Results : The pre-test PSQI score in the control group is 6.88 ± 1.872 while in the treatment group is 7.63 ± 1.996. The results of the statistical test showed that the difference is not significant (p>0.05). The post-test PSQI score in the control group was 7.92 ± 2.888 while in the treatment group was 4.58 ± 1.886. The results of the statistical test showed that the difference is significant (p<0.05). In the control group, there is a slight increase in PSQI score which is not significant (p>0.05), while in the treatment group there is a significant decrease in PSQI score (p<0.05). Conclusion : There is a significant difference in the sleep quality score between control and treatment groups; the sleep quality of the treatment group is better than the control group.Key Words : Sleep quality, Skipping exercise, Pittsburgh Sleep Quality Index (PSQI)